Temporary dynamics of the change of land use and vegetation in the Juluapan watershed in the state of Colima - Meza-Rodríguez, Demetrio; Olguín-López, José Luis; Quintero-Gradilla, Shatya Devi; Sánchez-Rodríguez, Enrique Valente; Villalvazo-López, Víctor Manuel (REVISTA TERRA LATINOAMERICANA, 2023)
The study of the dynamic processes of the change of land use and vegetation is essential given the trends in the degradation processes of ecosystems. The Juluapan basin exhibits processes of change of land use and vegetation for more than 50 years, therefore, the objective of our study was to analyze the changes in land and vegetation use over time for the periods 1971 to 2010 and 2010 to 2018, with aerial and satellite images using Geographic Information Systems (GIS). The results obtained for the period of 1971-2010 show the loss of 752 hectares of shrub vegetation that represents 13.3% of the total area. For the 2010-2018 period, a loss of 202 hectares was estimated, with a deforested area of 3.6%. The exchange rate for tree vegetation of the 1971-2010 period was defined with -1.47% and for the 2010-2018 period with a -2.03%. The scenarios of change of land use and vegetation presented in this study will allow the development of actions in favor of soil resource planning related to land use ordinance at the local level, as well as the execution of programs that reduce the impact on natural resources and promote the rational use of ecosystems in this region.